Collaborative governance in waste management: a case study in the municipality of Yogyakarta, Indonesia - Sabarna, Muhammad Akbar Nugraha; Ramdani, Rijal (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
The increasing waste problem in Indonesia, especially in Yogyakarta, has encouraged the implementation of collaborative waste management efforts. This research examines the driving factors behind the collaborative governance of the “Mbah Dirjo” program in Yogyakarta City, using Emerson’s Collaborative Governance Regimes framework: Leadership, Consequential Incentives, Interdependence, and Uncertainty. Qualitative research methods were used, with data collection through interviews, participatory observation, and document analysis. The research findings revealed that leadership plays an important role in mobilising collaborative efforts among stakeholders, including the Environment Department, Forum Bank Sampah, surrounding communities, and Teak Plastic Enterprises. Consequential incentives, such as funding and resource sharing, encourage participation from each party involved in the waste management collaboration. Interdependence among stakeholders ensures effective coordination in the implementation of Mbah Dirjo, while uncertainty presents challenges, such as the difficulty of changing people’s behavior in waste management. Despite these challenges, the Mbah Dirjo program has significantly improved waste reduction efforts. This research contributes to the understanding of collaborative governance in environmental management and highlights the importance of stakeholder synergy in addressing urban waste issues.